Successful management of Churg–Strauss syndrome using omalizumab as adjuvant immunomodulatory therapy: First documented pediatric case. Issue 3 (8th October 2013) - Iglesias, E.; Camacho Lovillo, M.; Delgado Pecellín, I.; Lirola Cruz, M.J.; Falcón Neyra, M.D.; Salazar Quero, J.C.; Bernabeu‐Wittel, J.; González Valencia, J.P.; Neth, O.
Summary Churg–Strauss syndrome (CSS) is an anti‐neutrophil cytoplasmic antibody (ANCA) associated vasculitis; it is extremely rare in childhood and defined according to the Chapel–Hill Consensus as an eosinophil‐rich and granulomatous inflammation involving the respiratory tract and necrotizing vasculitis affecting small to medium‐sized vessels. Children commonly have a history of asthma and sinusitis whilst clinical presentation typically involves pulmonary tract and less frequently skin, heart, gastrointestinal tract, and peripheral nerves. Cardiopulmonary disease is higher in children and prognosis is worse. It is associated with significant eosinophilia and raised serum IgE‐levels. ANCA are only found in 25% of childhood cases. Here we report the case of a 10‐year‐old girl who presented to us with vomiting, abdominal pain, and weight loss, paresthesias of lower extremities and breathlessness as well as a history of asthma, sinusitis and allergic rhinitis. She was treated with corticosteroids, cyclophosphamide, intravenous immunoglobulin, mycophenolate mofetil (MMF), and rituximab. However, remission was only achieved after initiation of omalizumab therapy, a recombinant humanized anti‐IgE antibody. To the best of our knowledge this is the first pediatric patient suffering from CSS successfully managed with adjuvant anti‐IgE therapy resulting in the control of respiratory as well as gastrointestinal symptoms. Pediatr Pulmonol. 2014; 49:E78–E81. © 2013 Wiley Periodicals, Inc.